Pengembangan Bahan Ajar Menulis Cerita Pendek Menggunakan Metode Alih Wahana untuk Siswa Kelas XI - Fitra Nur Fadila (Universitas Negeri Malang, 2021)
Abstract: The background behind this research on the development of teaching materials to write short stories using the vehicle transfer method is the result of a needs analysis conducted by researchers by observing learning activities in class, as well as interviews with one of the Indonesian Language teachers and class XI students at SMAN 1 Tumpang, Malang Regency. Based on the results of observations and interviews that have been conducted, the researcher found that the activities in the classroom still tend to be monotonous and students find it difficult to find short story ideas so that the themes developed are less varied. The purpose of this research development is to produce teaching materials to write short stories using the vehicle transfer method by referring to the content description, systematic, linguistic, and appearance that is appropriate for learning. This study uses the ADDIE development model. ADDIE development procedures consist of (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Based on the results of the feasibility test, this teaching material product received an average score of 90.05% which has product criteria that are very feasible to be implemented in learning activities. Keywords: teaching material, writing short stories, transferring, class XI students Abstrak: Hal yang melatarbelakangi penelitian pengembangan bahan ajar menulis cerita pendek menggunakan metode alih wahana ini adalah hasil analisis kebutuhan yang dilakukan peneliti dengan cara melakukan pengamatan terhadap kegiatan pembelajaran di kelas, serta wawancara kepada salah satu guru Bahasa Indonesia dan siswa kelas XI di SMAN 1 Tumpang, Kabupaten Malang. Berdasarkan hasil pengamatan dan wawancara yang telah dilakukan, peneliti menemukan bahwa kegiatan di dalam kelas masih cenderung monoton serta siswa merasa kesulitan dalam menemukan ide cerita pendek sehingga tema yang dikembangkan kurang bervariatif. Tujuan penelitian pengembangan ini adalah menghasilkan produk bahan ajar menulis cerita pendek menggunakan metode alih wahana dengan mengacu pada deskripsi isi, sistematika, kebahasaan, dan tampilan yang layak untuk pembelajaran. Penelitian ini menggunakan model pengembangan ADDIE. Prosedur pengembangan ADDIE terdiri atas (1) analisis, (2) desain, (3) pengembangan, (4) implementasi, dan (5) evaluasi. Berdasarkan hasil uji kelayakan, produk bahan ajar ini mendapat rata-rata skor 90,05% yang memiliki kriteria produk sangat layak untuk diimplementasikan dalam kegiatan pembelajaran. Kata kunci: bahan ajar, menulis cerita pendek, alih wahana, siswa kelas XI